Electrical characterization of graphene oxide and organic dielectric layers based on thin film transistor - Karteri, Ibrahim; Karatas, Sukru; Yakuphanoğlu, Fahrettin (Elsevier Science Bv, 2014)
We have studied the electrical characteristics of graphene oxide based thin flim transistor with the polymer insulators such as polymethyl methacrylate (PMMA) and poly-4-vinylphenol (PVP). Graphene oxide (GO) nanosheets were prepared by using modified Hummers method. The structural properties of GO nanosheets were characterized with Ultraviolet Visible (UV-vis), FT-IR spectroscopy and X-rays diffraction (XRD). Graphene oxide based thin flim transistor (GO-TFT) was prepared by a spin-coating and thermal evaporation technique. The electrical characterization of GO-TFT was analyzed by output and transfer characteristics by using Keithley-4200 semiconductor characterization system (SCS). The graphene oxide based thin flim transistor devices show p-type semiconducting behavior. The mobility, threshold voltage, sub-threshold swing value and I-on/I-off of GO-TFT were found to be 0.105 cm(2) V-1 s(-1), -8.7V, 4.03 V/decade and 10, respectively. (C) 2014 Elsevier B.V. All rights reserved.
9th Nanoscience and Nanotechnology Conference (NANOTR) -- JUN 24-28, 2013 -- Erzurum, TURKEY
Keywords: Graphene oxide; Modified Hummers method; Thin film transistor